Investigating Senior High School Teachers’ and Students’ Perceptions on Project-Based Learning in English Class - Mismar M Pogaru; Chairil Anwar Korompot; Abdul Halim (Institut Agama Islam Negeri Palopo, 2023)
This study focused on the teachers’ and students’ perceptions toward the implementation of Project- Based Learning in English class that was conducted at senior high school one of Luwu Timur. Mixed method was used to derive quantitative and qualitative data from surveys, an interview, and observational data. The research was mixed method that used quantitative and qualitative data. The instruments were questionnaire and interview to examine the students’ and teacher’s perceptions. The participants included 3 teachers and 13 students of exact class. This research was conducted for 3 months in which the teachers implemented projects in the classroom. The results showed that the teacher had a positive experience implementing Project Based Learning in teaching English as foreign language. Moreover, the teacher also found that Project- Based Learning was an effective way and successful in teaching English since the teacher can motivate the students to learn English. Furthermore, the students also supported that they were happy and enjoy when they learned English. Their considered the PjBL method to be successful, likable, and an effective way to learn English. In sum up, Project- Based Learning was the solution to make the process of learning English more effective and meaningful for senior high school students. This research supports the implementation of Project- Based Learning in an EFL context at SMAN 1 Luwu Timur. Key Words : Investigating, Project-Based Learning, English Class